Bonding strength performance of bamboo-based composite materials: an in-depth insight for sustainable construction applications - Sewar, Yousef; Amran, Mugahed; Avudaiappan, Siva; Gamil, Yaser; Rashid, Raizal S.M. (Elsevier, 2024)
This review systematically examines the multitude of factors influencing bonding strength in bamboo-based composite materials, given the rising prominence of bamboo as a green building material. With bamboo's inherent variability in mechanical properties and structure, engineered bamboo products have emerged to address challenges related to connections and joints. Such advancements have necessitated a detailed exploration of adhesive systems, a significant cost determinant in bamboo production. The adhesive bonding mechanism in bamboo, akin to wood, involves intricate processes including adhesive spreading, penetration, and solidification, influenced by the unique chemical composition of bamboo. The interfacial bond quality plays a pivotal role in determining the durability and performance of the final products, with numerous factors such as bamboo species, layered structure, adhesive type, and treatment types impacting the mechanical properties. Particular attention is given to the disparities in physical and mechanical properties between the bamboo culm's core and shell layers, attributing complexities to the gluing process. Examining shear failure strength reveals its criticality in mechanical investigations, with variations in bonding strength affecting the outcome. The review underscores the need for consistent quality control and adept manipulation of these influential factors for the successful manufacture of bamboo-based products. A comprehensive discussion ensues on the variables controlling the bonding properties of the developed bamboo products, aiming to evaluate and highlight the optimal parameters and procedures essential for enhancing the quality and reliability of bamboo-based composite materials for sustainable construction applications.